Improving the Ability to Write Core and Transformative Sentences of Class VI Students of SDN Batu Belah Timur 1 - Syaiful Bahri; Kanisius Kami; Ida Bagus Putrayasa (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to determine and describe the improvement in the ability to write core sentences and transfirmative sentences in class VI students at SDN Batu Belah Timur I, Dasuk sub-district, Sumenep district, Madura. The research method in this study is a descriptive qualitative research method, using observation, interview and documentation data collection techniques to produce descriptive data in the form of written or spoken words from people and observed behavior. The activity of writing core and transformative sentences tested improving the ability to write core and transformative sentences of class VI students at SDN Batu Belah Timur I. Of the total number of students, 16 were able to understand the material of core sentences and transformative sentences effectively. Even though there were still 1-4 of the 16 students, there were still problems in working on the questions given, compared to the observation time, only a portion of the students were able to make sentences well and correctly, which could be counted on the fingers of one hand.